Officers of the Society (Journal of Labor Economics, 2017)
Previous articleNext article FreeOfficers of the SocietyPDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMore2017–2018 Board of OfficersPresident: Marjorie McElroy, Duke UniversityPresident-Elect: Joseph Altonji, Yale UniversityVice President: Katharine G. Abraham, University of MarylandExecutive Board (2016–2018):Jennifer Hunt, Rutgers UniversityChinhui Juhn, University of HoustonExecutive Board (2017–19): Jeffrey Smith, University of MichiganNicole Fortin, University of British ColumbiaDan Black, University of Chicago and NORC, ex officioPaul Oyer, Stanford University and the Journal of Labor Economics, ex officioSecretary-Treasurer: Maggie NewmanFellows of the Society of Labor EconomistsJohn AbowdKatharine AbrahamDaron AcemogluGeorge AkerlofJoseph AltonjiJoshua AngristOrley AshenfelterDavid AutorGary Becker*Marianne BertrandSandra BlackRebecca BlankFrancine BlauRichard BlundellGeorge BorjasJohn BoundCharles BrownKenneth BurdettGlen Cain*David CardPierre-Andre ChiapporiJanet CurrieSteven J. DavisJohn DiNardoRon EhrenbergHenry FarberRichard FreemanRoland G. FryerVictor FuchsRobert GibbonsClaudia GoldinReuben GronauRobert HallJohn HaltiwangerDan HamermeshEric HanushekJames HeckmanCaroline M. HoxbyGeorge Johnson*Lawrence KahnLawrence KatzJohn KennanAlan KruegerKevin LangRichard LayardEdward LazearThomas LemieuxShelly LundbergStephen MachinW. Bentley MacLeodThomas MaCurdyAlan ManningMarjorie McElroyCostas MeghirRobert MichaelJacob Mincer*Robert MoffittEnrico MorettiDale Mortensen*Richard MurnaneKevin MurphyDerek NealSteve NickellWalter Oi*John PencavelChristopher PissaridesRobert PollakCanice PrendergastMelvin Reder*Mark RosenzweigKathryn ShawRob ShimerJames SmithJeffrey SmithGary SolonFrank StaffordChris TaberPetra ToddRobert TopelJohn Van ReenenYoram WeissFinis WelchRobert WillisNew Fellows Elected in 2017Kerwin Kofi CharlesChristian DustmannRobert LaLonde Notes *. Deceased. Previous articleNext article DetailsFiguresReferencesCited by Journal of Labor Economics Volume 35, Number 3July 2017 Published for the Society of Labor Economists, Economics Research Center/ NORC Article DOIhttps://doi.org/10.1086/692686 © 2017 by The University of Chicago. All rights reserved.PDF download Crossref reports no articles citing this article.